Digital technologies for government -supported health insurance systems in Asia and the Pacific - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
Explores digital solutions that can support the core business processes of public health insurance operators in Asia and the Pacific. Examples from low- and middle-income countries in the region and beyond are drawn to demonstrate how digital solutions have improved health insurance management and administration.
Introduction - - Digital Health Financing Ecosystem - - Challenges in Adoption of Digital Health Technologies for Health Financing - - Learnings and Recommendations - - Conclusion - - Appendixes.
Keywords: Health insurance -- Mathematical models; Health insurance -- Finance; Health insurance -- Asia and the Pacific; Finance -- Insurance -- Health insurance